DAMPAK SOSIAL EKONOMI RELOKASI PEDAGANG KAKI LIMA DI KAWASAN SIMPANG LIMA DAN JALAN PAHLAWAN KOTA SEMARANG - Aji Wahyu Heriyanto (Economics Development Analysis Journal, 2012)
The aim of  this research is to know how much is the socio-economic impacts relocation of  street vendors at the intersection of  Simpang Lima and Pahlawan streets of  Semarang City. This research used inferensial analysis and  deskriptif  percentase. To know the socio-economic impacts, it was done by interviewing and questionairring some street vendors at the intersec-tion of  Simpang Lima and Pahlawan streets of  Semarang City. The result of  this research showed that the social impact of  the relocation of  street vendors at the intersection of  Sim-pang Lima and a Pahlawan streets of  Semarang City a positive impact in terms of  the social economy that is improve social relationships among traders, feasibility and convenience of  business and can increase the income of  street vendors. Still a constraint in terms of  infra-structure and facilities faced by street vendors after the relocation government as the manager is expected to be assisted with street vendors rapid response in dealing with the damage to shelter by repairing the damaged parts and providing adequate parking space.